Geographical distribution and prevalence of tick‐borne encephalitis virus in questing Ixodes ricinus ticks and phylogeographic structure of the Ixodes ricinus vector in Norway. (29th February 2020) - Vikse, Rose; Paulsen, Katrine M.; Edgar, Kristin Skarsfjord; H.‐O. Pettersson, John; Ottesen, Preben Skrede; Okbaldet, Yohannes Bein; Kiran, Nosheen; Lamsal, Alaka; Lindstedt, Heidi Elisabeth H.; Pedersen, Benedikte Nevjen; Soleng, Arnulf; Andreassen, Åshild K.
Abstract: The tick‐borne encephalitis virus (TBEV), a zoonotic flaviviral infection, is endemic in large parts of Norway and Eurasia. Humans are mainly infected with TBEV via bites from infected ticks. In Norway, the main geographical distribution of ticks is along the Norwegian coastline from southeast (~59°N) and up to the southern parts of Nordland County (~65°N). In this study, we collected ticks by flagging along the coast from Østfold County to Nordland County. By whole‐genome sequencing of the mitochondrial genome of Ixodes ricinus, the phylogenetic tree suggests that there is limited phylogeographic structure both in Norway and in Europe. The overall TBEV prevalence is 0.3% for nymphs and 4.3% for adults. The highest estimated TBEV prevalence in adult ticks was detected in Rogaland and Vestfold County, while for nymphs it is highest in Vestfold, Vest‐Agder and Rogaland. The present work is one of the largest studies on distribution and prevalence of TBEV in ticks in Scandinavia, showing that the virus is wider distributed in Norway than previously anticipated.